Mechanisms of α-mangostin-induced antinociception in a rodent model - Mohd. Sani, Mohd. Hijaz; Bakhtiar, M. Taher; Darnis, Deny Susanti; Lay Kek, Teh; Salleh, Mohd Zaki; Zakaria, Zainul Amiruddin (SAGE, 2015)
Objective: Elucidate the antinociceptive mechanisms of a-mangostin isolated from Garcinia malaccensis Linn. Methods: Male mice/rats (n 1⁄4 6/group) were used in this between-group study. To determine a-mangostin’s antinociceptive profile, animals were given a-mangostin orally (3, 30, or 100 mg/kg) 60 min before the start of the abdominal constriction or formalin tests. In the hot plate test, the noxious stimulus was applied before and 60, 90, 120, 150, 180, and 210 min after treatment with test solutions. Positive controls received 100 mg/kg acetylsalicylic acid (ASA; oral) or 5 mg/kg morphine (intraperitoneal injection) for the abdominal constriction and hot plate tests, respectively, and either ASA or morphine for the formalin test. Negative controls received vehicle only. To explore a-mangostin’s mechanisms of action, we performed (i) the hot plate test with naloxone (5 mg/kg) pretreatment to verify involvement of opioid receptors; (ii) the abdominal constriction test with 20 mg/kg L-arginine, NG-nitro-L-arginine methyl esters (L-NAME), methylene blue (MB), L-arginine plus L-NAME, or L-arginine plus MB or 10 mg/kg glibenclamide pretreatment to verify involvement of the L-arginine/nitric oxide (NO)/cyclic guanosine monophosphate (cGMP) and Kþ-ATP pathways; and (iii) the paw-licking test using capsaicin (1.6 μg capsaicin/paw), glutamate (10 μmol glutamate/paw), or phorbol 12-myristate 13-acetate (PMA; 0.05 mg/paw) to verify involvement of vanilloid receptors, the glutamatergic system, and protein kinase C (PKC). Results: a-mangostin significantly inhibited nociception (p < .05) in all models. Only naloxone, L- arginine, methylene blue, PMA, and glibenclamide affected a-mangostin antinociception significantly (p < .05). Conclusion: a- mangostin exhibits peripheral and central antinociception through modulation of opioid and vanilloid receptors, the glutamatergic system, and the L-arginine/NO/cGMP/PKC/Kþ-ATP pathways.